Connexin43 Hemichannels in Satellite Glial Cells, Can They Influence Sensory Neuron Activity? - Retamal, Mauricio A.; Riquelme, Manuel A.; Stehberg, Jimmy; Alcayaga, Julio (Frontiers in Molecular Neuroscience, 2017)
In this review, we summarize the current insight on the role of Connexin- and Pannexin-based channels as modulators of sensory neurons. The somas of sensory neurons are located in sensory ganglia (i.e., trigeminal and nodose ganglia). It is well known that within sensory ganglia, sensory neurons do not form neither electrical nor chemical synapses. One of the reasons for this is that each soma is surrounded by glial cells, known as satellite glial cells (SGCs). Recent evidence shows that connexin43 hemichannels and probably pannexons located at SGCs have an important role in paracrine communication between glial cells and sensory neurons. This communication may be exerted via the release of bioactive molecules from SGCs and their subsequent action on receptors located at the soma of sensory neurons. The glio-neuronal communication seems to be relevant for the establishment of chronic pain, hyperalgesia and pathologies associated with tissue inflammation. Based on the current literature, it is possible to propose that connexin43 hemichannels expressed in SGCs could be a novel pharmacological target for treating chronic pain, which need to be directly evaluated in future studies.